The Merck manual of diagnosis and therapy - Beers, Mark H.; Berkow, Robert, 1929-; Bogin, Robert M.; Fletcher, Andrew J.; Nace, Barbara Amelia; Moy, Daniel E.; Merck Research Laboratories (Whitehouse Station, NJ : Merck, 1999)
Presents the full-text of the "Merck Manual of Diagnosis and Therapy," Seventeenth Edition, Centennial Edition, published by Merck and Co., Inc. in Whitehouse Station, New Jersey. Offers searchable medical information.
Title from Web page as viewed on Apr. 2, 2002.
Internet edition provided by Medical Services, USMEDSA, USHH ; Site designer and HTML author Barbara Amelia Nace ; programmer, Daniel E. Moy.
Also available in print.
Keywords: Medicine -- Handbooks, manuals, etc